Tenses Usage in Sherlock Holmes Short Story by Sir Arthur Conan Doyle - Hilda Hastuti; Diah supatmiwati (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Tense one of grammatical terms in language learning, especially English which is used to show an event, activity, or scenario is occurring. The main tenses in English are past tense, present tense, and future tense. Tenses are used in writings and non-writings. Tenses have a very important role in writing English fiction, such as in writing short stories. This research was conducted to find out the tenses used in the book a collection of short stories series 1 of Sherlock Holmes which consists of 6 chapters and 174 pages. This was analysed using Betty Schrampfer Azar’s Theory. The method used in this research was qualitative method. The research results showed that there were 1285 data from chapters 1 to chapter 6 consisting of 503 present tenses, 705 past tenses and 77 future tenses. The simple past tense is used in most of the sentences and the simple future tense are the least used in the sentences of the book.